2016
DOI: 10.1155/2016/4626382
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Renal Function Decline of Patients with Type 2 Diabetes

Abstract: Aims. We aimed to investigate the sex differences in the renal function decline among patients with type 2 diabetic mellitus (T2DM), focusing on the differences in the risk factors at early stage of renal dysfunction. Methods. A clinic-based retrospective longitudinal study (follow-up duration: 8.1 ± 1.4 years) was conducted to assess the sex differences in the annual estimated glomerular filtration rate (eGFR) change in 344 (247 male and 97 female) Japanese T2DM patients. The sex differences in the risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 31 publications
3
24
2
3
Order By: Relevance
“…56 In a small (247 male, 97 female adults with T2DM) clinic-based, retrospective longitudinal study (follow-up duration, 8.1AE1.4 years), the mean annual eGFR change was À3.5AE2.7%/year in females and À2.0AE2.2%/year in males. 49 This eGFR decline was associated with HbA 1c and lowdensity lipoproteinecholesterol levels, but only in females, suggesting a need for a more aggressive therapeutic intervention to improve metabolic profiles at early stage, especially in females. Another study, conducted in women with T2DM (mean age, 61.6AE6.8 years; duration of diabetes, 9.8AE7.2 years) found that the early renal functional decline in these women is linked to increased vascular stiffness, which may be associated with visceral fat accumulation as determined by waist circumference.…”
Section: Evidence For the Female Sex As A Risk Factor For Dkd Associamentioning
confidence: 89%
See 2 more Smart Citations
“…56 In a small (247 male, 97 female adults with T2DM) clinic-based, retrospective longitudinal study (follow-up duration, 8.1AE1.4 years), the mean annual eGFR change was À3.5AE2.7%/year in females and À2.0AE2.2%/year in males. 49 This eGFR decline was associated with HbA 1c and lowdensity lipoproteinecholesterol levels, but only in females, suggesting a need for a more aggressive therapeutic intervention to improve metabolic profiles at early stage, especially in females. Another study, conducted in women with T2DM (mean age, 61.6AE6.8 years; duration of diabetes, 9.8AE7.2 years) found that the early renal functional decline in these women is linked to increased vascular stiffness, which may be associated with visceral fat accumulation as determined by waist circumference.…”
Section: Evidence For the Female Sex As A Risk Factor For Dkd Associamentioning
confidence: 89%
“…Kajiwara et al 49 The mean decline in annual eGFR was -3.5AE2.7%/year in females and -2.0AE2.2%/year in males (P<0.001) and was associated with HbA 1c and low-density lipoprotein cholesterol levels, but only in women.…”
Section: Greater Risk In Womenmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study determined that females with chronic kidney disease (CKD) had a slower decline in glomerular filtration rate (GFR), lower risk of progression to end-stage renal disease (ERSD), and a lower risk of death compared to age-matched men with similar mild-to-moderate CKD [42]. In diabetic kidney disease, men tended to demonstrate renal complications roughly 10 years earlier than women [40], while sex differences in obesity-related kidney disease [43][44][45] demonstrated that female sex hormones may safeguard against worsening pathology [45]. Thus, being female may have a protective effect on the kidney, preventing women from developing the more severe phenotypes observed in men.…”
Section: Urate As a Risk Factor In Diseasementioning
confidence: 99%
“…In studies that enrolled patients with type 2 diabetes, it seems that more results indicated female has greater risk of DKD progression [8] . A study from Japan [12] (247 male and 97 female)…”
Section: Discussionmentioning
confidence: 99%